Studies On Genetic Divergence In Maize (Zea mays) Inbreds (Bangladesh Journal of Agricultural Research, 2013)
Genetic divergence in 17 CIMMYT Maize inbred lines including one check were assessed based on some morphological traits and grain yield using Mahalanobis D2-statistics. The experiment was carried out in alpha lattice design with two replications at Regional Agricultural Research Station, Ishurdi Pabna during the winter 2010-2011. The genotypes were grouped into four clusters. The cluster II contained the highest number of lines (6), while the cluster I contained only single genotype. The maximum inter-cluster distance was noticed between the cluster I and IV and minimum between cluster I and II. The highest intra-cluster distance was observed in the cluster IV and lowest in cluster I. The genotypes in the cluster III showed better performances having shorter growth duration, short stature, shortest ear height, better shelling percentage and reasonable yielding ability. It is expected that crossing of inbred lines belonging high to medium D2 values may tend to produce high heterosis for yield. Ear aspect had the greatest contribution to the genetic divergence. Days to pollen shedding, silking, maturity, and 1000-grain weight were found to be responsible for primary differentiation. Bangladesh J. Agril. Res. 38(1): 71-76, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15191